Zeta Potential, Effective Membrane Charge and Donnan Potential for TiO2 NF Ceramic Membrane (Journal of Engineering, 2018)
Nanofiltration (NF) ceramic membrane have found increasing applications particularly in wastewater and water treatment. In order to estimate and optimize the performance of NF membranes, the membrane should be characterized correctly in terms of their basic parameters such as effective pore radius (rp) and equivalent effective thickness as well as effective surface charge ( ), the effective charge density ( ) and Donnan potential ( ). The impact of electrokinetic (zeta) potential on the membrane surface charge density, effective membrane charge density and Donnan potential at two different concentrations of the reference solutions 0.001, 0.01 M sodium chloride at various pH values from 3 to 9, and effective pore radius (rp) for nominal 0.9 nm  ceramic TiO2 NF membrane were evaluated. Experiments were conducted at cross flow (1.0 m/s) using Microelectrophoresis technique for measuring membrane zeta potential, effective pore radius, and Donnan steric pore model (DSPM). The TiO2 membrane isoelectric point (net membrane charge equals zero) was found at pH of 3.7, 3.5 for 0.001 and 0.01 M NaCl respectively. The results showed that the NF membrane zeta potential changes its sign from positive to negative after the isoelectric point. The evaluated effective pore radius was found to be equal to 0.56 nm by using (DSPM) and the membrane equivalent effective thickness equals to (2×10-6 m).